Development of a joint TQM&IlT implementation model - Georgousis, Ioannis D. (Cranfield University, 1997)
This study investigates the impact of the joint TQM and JIT approach on the performance of manufacturing organisations. The final objective is the development of a Joint TQM&JIT Implementation Model, based on the results of the investigation. The Model will contain a series of activities and operations that will lead to process and product improvement, based on the principles of the joint implementation approach. Many studies and researches have been conducted in order to investigate and clarify the details and the potential benefits of each system. However, few studies looked at the operations that are necessary for a successful joint TQM and JIT approach; and even if they did it, they did not analyse the manufacturing process systematically. The present study attempts to give an answer to this problem and, moreover, to produce a systematic, analytical, and clear implementation plan. The literature review and the industrial survey showed that there is a very close link between TQM and JIT; what is missing is a detailed implementation plan. The TQM&JIT Model tries to satisfy the musts and the wants of every manufacturing organisation which wishes to be competitive and world-class in the contemporary demanding markets, using the quality of the products and the low manufacturing cost as weapons. Furthermore, the Model details the sequence of the activities that should be followed in order to get completely beneficial results. It determines the production areas that should be improved, but also determines the role of everyone within the company towards that objective. The flowchart that presents the network of the activities is very simple and very clear, and this is perhaps the major advantage of the Joint TQM&JIT Implementation Model. A series of performance measures for each step of the Model has also been developed, in order to ensure the completion of each implementation stage.